(untitled) (Community Based Medical Journal, 2015)
Day by day road traffic accident in Bangladesh is increasing. Mymensingh-Dhaka highway passes beside the Community Based Medical College Hospital, Bangladesh. We often have to manage a greater number of traumatic patients. In road traffic accident the incidence of fracture shaft of femur is the most common. That’s why my study was done to evaluate the result of management of fracture shaft of the femur with antegrade interlocking intramedullary nailing under the department of Orthopedic Surgery in CBMCH,B in the period between January 2009 to July 2013. Total 88 patients were selected for interlocking nailing initially in the study. Out of them 8 patients did not report in subsequent follow up. So the result of the study was based on 80 patients (48 males; 32 females) with the range of 20- 68 years of age. The average age of the patient was 36 years. Motor vehicle accidents was the most common cause of fracture shaft femur (65%) and the second most common cause was fall from height (20%) specially fall from tree. Among the patients; right sided femur involvement was 67.5% (54) and left sided femur involvement was 32.5% (26). The majority fracture of the shaft of the femur was lower third (70%). The patients were mostly in the day-laborers’ groups (35%), and, the next group was students. The mean union time was 18 weeks with the range of 15-30 weeks. After operation, complications were found such as; infection 3.75%(3), non-union 1.25% (1). Excellent functional outcome was found in 82.5% (66), good in 12.5% (10), fair in 5%(4). This functional outcome study was evaluated by Klemm & Borner 1 criteria. CBMJ 2015 January: Vol. 04 No. 01 P: 13-17